A Case of Chronic Ethylene Glycol Intoxication Presenting without Classic Metabolic Derangements. (21st August 2014) - Toth-Manikowski, Stephanie M.; Menn-Josephy, Hanni; Bhatia, Jasvinder
Abstract : Acute ethylene glycol ingestion classically presents with high anion gap acidosis, elevated osmolar gap, altered mental status, and acute renal failure. However, chronic ingestion of ethylene glycol is a challenging diagnosis that can present as acute kidney injury with subtle physical findings and without the classic metabolic derangements. We present a case of chronic ethylene glycol ingestion in a patient who presented with acute kidney injury and repeated denials of an exposure history. Kidney biopsy was critical to the elucidation of the cause of his worsening renal function.